¿Mucha estrategia, poca implementación? - Gutiérrez Rodríguez, Juan Manuel; Pérez López, J. Jésus; Guerra Orona, Rebeca (Realidades Revista de la Facultad de Trabajo Social y Desarrollo Humano, 2017)
Pendiente